Adolescent and young adult patients as co‐researchers: A scoping review. (15th May 2021) - Fløtten, Kjersti J. Ø.; Guerreiro, Ana Isabel Fernandes; Simonelli, Ilaria; Solevåg, Anne Lee; Aujoulat, Isabelle
Abstract: Background: As part of a research project aimed at evaluating a hospital‐based adolescent transition programme, we asked ourselves what is known about the ethical and methodological challenges of research involving adolescent patients as co‐researchers. The aim of our review was to summarize empirical evidence and identify knowledge gaps about the involvement of young patients as co‐researchers. Methods: We conducted a scoping review through searches in MEDLINE, EMBASE, PsychINFO, AMED. Results: We found reports of young patients being actively engaged as co‐researchers in any stage of a research project, although commonly they were not involved in every stage. Including young patients as co‐researchers is resource demanding and time‐consuming. Involving young patients as co‐researchers contributes to the fulfilment of their right to participation and may improve the relevance of research. Benefits for the young co‐researcher include empowerment, skills building and raised self‐esteem. Few authors go into detail about ethical considerations when involving young co‐researchers. None of the included articles discuss legal considerations. Discussion and conclusion: No lists of recommendations are given, but recommendations can be deduced from the articles. There is need for time, funding and flexibility when including young patients as co‐researchers. Knowledge gaps concern legal and ethical dilemmas of including a vulnerable group as co‐researchers. More reflection is needed about what meaningful participation is and what it entails in this context. Patient or Public Contribution: This review is part of a research project where the hospital youth council has been involved in discussions of focus area and methods.